Analysis of polyarylate ardel ®D-100 films undoped and doped by BF-4 as a function of the doping concentration - Serin, M; Sakar, D; Cankurtaran, O; Karaman, F (NATL INST OPTOELECTRONICS, 2005)
The polyarylate films were characterized in terms of its electrical properties depending on doping effect for the films having three different dopant concentration of 0.25 mol, 0.50 mol and 1.00 mol per mot of polymer and with the constant sample thickness of 6 mu m. The glass transition temperatures of undoped and doped Ardel((R))D-100 were determined from conductivity measurements. It was aimed to observe the doping effect on glass transition temperature. In addition, dielectric constant, dipol moment and solubility parameter of undoped polymer were determined by means of group contribution method as well. The solubility parameter of polymer, delta calculated from group contribution method was compared with data found by inverse gas chromatography.
Keywords: ardel; glass transition temperature; electrical characterization; dark conductivity; doping effect; ELECTRICAL-CONDUCTIVITY MEASUREMENTS; TEMPERATURE; GLASSES; Materials Science; Optics; Physics